Probabilistic Model of Liquefaction in Serpong and Its Impact on Nuclear Installation Safety - Haifani, A. M.; Prakoso, W.; Setiadipura, T.; Suntoko, H.; Muhammad, A. G. (National Research and Innovation Agency, 2026)
This study delivers the first full probabilistic liquefaction hazard assessment specifically for an Indonesian nuclear power station (NPP) site, filling a major gap in current geotechnical risk evaluation techniques for nuclear infrastructure. We want to assess liquefaction risk under seismic loading in the Serpong region, a potential site for future NPP development, by integrating seismic hazard data and geotechnical site characteristics. The technique includes Probabilistic Seismic Hazard Analysis (PSHA), Ground Motion Prediction Equations (GMPEs), disaggregation curves, and soil characteristics extracted from 18 boreholes, such as SPT-N values, fines content, and groundwater level changes. Liquefaction triggering is assessed using Cyclic Stress Ratio (CSR), Cyclic Resistance Ratio (CRR), and associated factors (MSF, Rd), followed by probabilistic validation. Over a 50-year exposure period, the total liquefaction probability ranges from 0.5676 to 0.594, with the maximum vulnerability seen in water-saturated sandy layers at depths of 1-6 meters. These findings emphasize localized seismic susceptibility and have direct implications for risk-informed NPP foundation design and regulatory safety evaluations. Furthermore, the findings can be integrated into Probabilistic Safety Assessment (PSA) frameworks to help with quantitative risk indicators like Core Damage Frequency (CDF) and Large Early Release Frequency (LERF). This study provides a reproducible methodology for assessing liquefaction at nuclear plants in other seismically active regions.